Ultrahigh molecular weight polyethylene with uniform particle size distribution and preparation method thereof
Through the prepolymerization process and catalyst optimization, the two-kettle series process and a specific catalyst system are adopted to solve the problem of difficult to prepare ultra-high molecular weight polyethylene with consistent particle size distribution in the prior art, and high consistency and excellent performance products are achieved.
Patent Information
- Application Number
- CN202411572154.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
AI Technical Summary
It is difficult to prepare ultra-high molecular weight polyethylene with consistent particle size distribution in the prior art, especially in slurry processes using Ziegler-Natta catalysts, and it is difficult to achieve high consistency products.
Through the prepolymerization process and catalyst optimization, a process flow of two kettles is adopted to perform low-temperature prepolymerization in the first reactor, and then polymerization in the second reactor. The catalyst system includes titanium tetrachloride doped with magnesium compound as the main catalyst, triethylaluminum and diethylaluminum chloride as the cocatalyst, and siloxane-based compounds as electron donors.
A high-quality ultra-high molecular weight polyethylene with consistent particle size distribution is achieved, with a viscosity average molecular weight of 1.45 to 1.55 million, a particle size of 60 to 90 μm, and a particle size distribution index (PDI) of 0.2 to 0.3, which significantly improves the consistency of the product. and performance.
Smart Images

Figure CN119431633A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polyethylene technology, in particular to ultra-high molecular weight polyethylene with consistent particle size distribution and a preparation method thereof. Background Art
[0002] Polyethylene and its copolymers are widely used in packaging, film, pipe, wire and cable and other fields due to their excellent physical and chemical properties. In recent years, with the growing demand for high-performance polyethylene and its copolymers, researchers have been exploring new catalyst systems and polymerization processes to improve the activity, selectivity and performance of the catalyst. In polymerization reactions, the selection and performance of catalysts are crucial to controlling the structure and properties of polymers. A typical polyethylene catalyst system usually includes a main catalyst, a co-catalyst and an electron donor.
[0003] Although the existing catalyst systems and carrier materials have met the needs of polymerization reactions to a certain extent, there are still some challenges: how to further improve the activity of the catalyst to reduce production costs; how to regulate the microstructure of the polymer by improving the catalyst system and thereby improve the physical and chemical properties of the product are all topics that R&D personnel need to study in depth.
[0004] In addition, the market is in urgent need of high-end polyethylene, especially in the fields of medical treatment, new energy battery separator materials, high-end filter materials, etc., which place high demands on the super consistency of polyethylene (microstructure consistency, molecular weight consistency, particle size consistency). Since Ziegler-Natta catalyst is a multi-active center catalyst, it is difficult to prepare highly consistent ultra-high molecular weight polyethylene using the catalyst through the slurry process, so further improvements are needed in the preparation process. Summary of the invention
[0005] In order to solve the defects in the prior art, the present invention provides an ultra-high molecular weight polyethylene with uniform particle size distribution and a preparation method thereof, and prepares high-quality ultra-high molecular weight polyethylene with super uniform particle size distribution through prepolymerization process and catalyst optimization.
[0006] The present invention is achieved through the following technical solutions:
[0007] A method for preparing ultra-high molecular weight polyethylene with consistent particle size distribution comprises the following steps:
[0008] S1, adding hexane into the first reactor as a solvent, adding a catalyst, raw material ethylene and hydrogen into the first reactor to carry out a prepolymerization reaction;
[0009] S2, after the prepolymerization reaction, the reaction slurry discharged from the first reactor enters the second reactor for polymerization reaction;
[0010] S3, after the polymerization is completed, the reaction slurry discharged from the second reactor is post-treated to obtain a finished product;
[0011] Wherein, the catalyst described in step S1 includes a main catalyst, a co-catalyst and an electron donor;
[0012] The main catalyst is titanium tetrachloride doped with a magnesium compound;
[0013] The co-catalyst is triethylaluminum and / or diethylaluminum chloride supported by alumina;
[0014] The electron donor is a siloxane compound.
[0015] As a preferred technical solution of the present invention, the molar ratio of the main catalyst, the co-catalyst and the electron donor is 1:50-100:1-10, preferably, the molar ratio of the main catalyst, the co-catalyst and the electron donor is 1:75-100:3-6.
[0016] As a preferred technical solution of the present invention, in the main catalyst, the molar ratio of the magnesium compound to titanium tetrachloride is 0.01 to 1:1, preferably, the molar ratio of the magnesium compound to titanium tetrachloride is 0.1 to 0.5:1, and the magnesium compound includes magnesium chloride, magnesium bromide, magnesium iodide, and diethoxymagnesium. Preferably, the magnesium compound is magnesium chloride. The crystal structure of MgCl2 is similar to that of TiCl4. TiCl4 and MgCl2 can form a eutectic well and interact to form an active center, which helps to improve the catalytic activity.
[0017] As a preferred technical solution of the present invention, the co-catalyst is a mixture of triethylaluminum supported on alumina and diethylaluminum chloride supported on alumina, the molar ratio of triethylaluminum to diethylaluminum chloride is 2:1 to 3, preferably, the molar ratio of triethylaluminum to diethylaluminum chloride is 2:3.
[0018] The inventor has found that using triethylaluminum and diethylaluminum chloride supported by alumina as co-catalysts can help improve the particle size state of polyethylene. The inventor speculates that the possible reason is that the combination of triethylaluminum and diethylaluminum chloride can activate TiCl4 and improve the catalytic activity. The alumina carrier provides a large surface area and good thermal stability, which is conducive to the dispersion and stability of the catalytic active center. Among them, triethylaluminum, as a strong reducing agent, can promote the reduction of TiCl4 and form a more active catalytic center; diethylaluminum chloride, as an electron donor, regulates the electronic environment of the titanium source by interacting with TiCl4, affects the activity and selectivity of the catalyst, and improves the performance of the polymer product, such as molecular weight distribution and crystallinity. Triethylaluminum and diethylaluminum chloride play a complementary role in the catalyst system. Triethylaluminum improves the activity of the catalyst through reduction, and diethylaluminum chloride improves the selectivity of the catalyst by adjusting the electronic environment. The result of the joint action of the two improves the overall performance of the catalyst and improves the molecular morphology of the polymer product.
[0019] As a preferred technical solution of the present invention, the preparation method of alumina-loaded triethylaluminum and alumina-loaded diethylaluminum chloride is: adding an alumina carrier to a solution containing triethylaluminum or diethylaluminum chloride, soaking for a certain period of time under stirring to allow triethylaluminum or diethylaluminum chloride to be uniformly adsorbed on the surface of the alumina, and drying and activating the loaded alumina carrier.
[0020] As a preferred technical solution of the present invention, the electron donor is a siloxane compound selected from tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, methyltriethoxysilane, ethyltriethoxysilane, n-propyltriethoxysilane, monochlorotriethoxysilane, 3-chloropropyltriethoxysilane, methyltrimethoxysilane, ethyltrimethoxysilane, isobutyltrimethoxysilane, hexyltrimethoxysilane, dimethyldimethoxysilane, diisopropyldimethoxysilane, dicyclohexyldimethoxysilane, cyclohexylmethyldimethoxysilane, diphenyldimethoxysilane, and phenylmethyldimethoxysilane.
[0021] Preferably, the electron donor is selected from cyclohexylmethyldimethoxysilane, methyltriethoxysilane, and ethyltriethoxysilane. Siloxane compounds (such as cyclohexylmethyldimethoxysilane) as an electron donor can interact with the titanium source, affect the coordination environment of the titanium source, and change the activity and selectivity of the final catalyst.
[0022] As a preferred technical solution of the present invention, in step S1, the catalyst is diluted with hexane to obtain a catalyst dilution solution, which is then added to the reactor, wherein the concentration of TiCl4 in the dilution solution is 0.1 to 10 mmol / L, preferably 0.1 to 1 mmol / L, and more preferably 0.1 to 0.5 mmol / L;
[0023] And / or, the volume ratio of hydrogen to ethylene is 0.0001 to 0.01:1, preferably, the volume ratio of hydrogen to ethylene is 0.001 to 0.005:1.
[0024] As a preferred technical solution of the present invention, the reaction conditions for the prepolymerization reaction in the first reactor in step S1 are: the temperature in the reactor is controlled at 30-50°C, the pressure is controlled at 0.2-0.8MPa, and the polymerization reaction time is controlled at 0.1-1h. Preferably, the temperature in the reactor is controlled at 35-45°C, the pressure is controlled at 0.45-0.6MPa, and the polymerization reaction time is controlled at 0.15-0.5h.
[0025] As a preferred technical solution of the present invention, the reaction conditions for the polymerization reaction in the second reactor in step S2 are: the temperature in the reactor is controlled at 70-90°C, the pressure is controlled at 0.2-0.8MPa, and the polymerization reaction time is controlled at 2-8h. Preferably, the temperature in the reactor is controlled at 75-85°C, the pressure is controlled at 0.45-0.6MPa, and the polymerization reaction time is controlled at 3-6h.
[0026] As a preferred technical solution of the present invention, the post-treatment in step S3 is: the slurry after the reaction is moved to a flash tank for product separation, the separated gas phase is sent to a recovery unit, and the separated solid phase polymer enters a degassing and drying unit, and the final product is obtained after drying.
[0027] The ultra-high molecular weight polyethylene obtained by the above-mentioned preparation method has a viscosity-average molecular weight of 1.45-1.55 million, a particle size of 60-90 μm, and a particle size distribution index (PDI) of 0.2-0.3.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] The present invention adopts an optimized catalyst system, and the main catalyst TiCl4 interacts with the magnesium compound to form an active center. For example, MgCl2 is adopted, and its crystal structure is similar to the TiCl4 crystal structure, and the two can form a eutectic structure, interact to form an active center, and improve catalytic activity. A mixture of triethylaluminum supported by alumina and diethylaluminum chloride supported by alumina is used as a cocatalyst. By using alumina as a carrier material, not only the stability of the reaction is improved, but also the uniform distribution of the product particle size is promoted. The high specific surface area and controllable pore structure of alumina provide a uniformly dispersed platform for the cocatalyst, thereby improving the activity and selectivity of the catalyst, making the polymerization reaction more controllable, and the particle size distribution of the final product is more consistent. In addition, by controlling the molar ratio of triethylaluminum and diethylaluminum chloride, the effective synergistic effect of the two cocatalysts is achieved. This synergistic effect improves the activity and stability of the catalyst, so that the product has a higher activation degree and better performance. Finally, the siloxane compound, as an electron donor, can interact with the titanium source, affect the coordination environment of the titanium source, and improve the activity and selectivity of the catalyst.
[0030] In addition, on the basis of catalyst optimization, the present invention adopts the form of two kettles in series to prepare ultra-high molecular weight polyethylene, firstly prepolymerizes at low temperature in the first reactor, in which the catalyst and the reaction raw materials are fully mixed in the reactor, and the catalyst is reformed in the process. Since the catalyst and the reaction raw materials are controlled by temperature, the reaction process is mild and controllable, avoiding the situation that the polymerization reaction is too fast and causes uneven products or incomplete crystallization, which is conducive to the uniform growth of polymer chains and improves the regularity and uniformity of the product. After the prepolymerization is completed, the second reactor is entered, and after the reaction temperature is increased, the fully mixed catalyst is increased to improve the reaction conversion rate, further uniformly grow the polymer chain, and finally obtain a product with consistent particle size distribution. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a schematic diagram of the process flow of the present invention. DETAILED DESCRIPTION
[0032] In order to enable those skilled in the art to better understand the technical solution of the invention, the present invention is further described in detail below in conjunction with specific implementation methods.
[0033]
Preparation of catalysts Y1 to Y5
[0034] Preparation of co-catalyst: triethylaluminum and diethylaluminum chloride are loaded on an alumina carrier, and the preparation is specifically carried out according to the following process:
[0035] Activation of alumina: Place the γ-alumina carrier in a porcelain boat and calcine it in a muffle furnace at 400°C for 2 hours to remove moisture and other volatile impurities.
[0036] Loading of triethylaluminum / diethylaluminum chloride: In a nitrogen-protected glove box, triethylaluminum / diethylaluminum chloride was dissolved in hexane (the volume ratio of triethylaluminum / diethylaluminum chloride to hexane was 1:5), an appropriate amount of activated alumina carrier was added to the triethylaluminum / diethylaluminum chloride solution, and immersed for 24 hours under magnetic stirring to ensure that triethylaluminum / diethylaluminum chloride was uniformly adsorbed on the surface of alumina, the loaded alumina carrier was dried at about 100°C for 24 hours, and the solvent hexane was removed to obtain the carrier.
[0037] Preparation of the main catalyst: The main catalyst is a titanium tetrachloride complex doped with magnesium chloride, which is prepared by the following method: anhydrous magnesium chloride is activated by ball milling, and the activated magnesium chloride is added to titanium tetrachloride to form a magnesium chloride-titanium tetrachloride complex.
[0038] Catalysts Y1 to Y5 are composed of a main catalyst, a co-catalyst and an electron donor in a compounded combination according to a certain proportion. Table 1 shows the specific proportions and compositions of catalysts Y1 to Y5. The catalysts are diluted with hexane to form a catalyst diluent before use.
[0039] Table 1 Specific composition of catalysts Y1 to Y5
[0040]
[0041]
Preparation of polyethylene E1~E5
[0042] The instruments or reagents in the examples of the present invention that do not indicate the manufacturer are all conventional commercial instruments or reagents. The experiments were carried out in a 2L stirred reactor as a small test device. The reactor was made of stainless steel and equipped with a heat exchange jacket. Figure 1 The process flow diagram of the present invention is shown in FIG. 2 , wherein two reactors are connected in series. During the experiment, a suitable amount of solvent hexane is added to the first reactor as the reactor bottom liquid, a catalyst diluent, raw materials ethylene and hydrogen are added to the first reactor, and the temperature in the reactor is controlled to carry out a prepolymerization reaction; after the prepolymerization reaction, the reaction slurry discharged from the first reactor enters the second reactor, and the temperature in the reactor is controlled to carry out a polymerization reaction; after the polymerization is completed, the reaction slurry discharged from the second reactor is post-treated to obtain a finished product.
[0043] The specific process of polymerization is as follows:
[0044] 1. After nitrogen is purged into the reaction system several times, about 1L of hexane is added into the first reaction kettle, and the temperature in the first reaction kettle is maintained at 30-50°C by temperature control;
[0045] 2. In a catalyst preparation tank, the catalyst (catalysts Y1 to Y5) and hexane are mixed evenly to form a catalyst dilution solution for standby use, and the concentration of TiCl4 in the catalyst dilution solution is 0.1 to 1 mmol / L, preferably 0.1 to 0.5 mmol / L;
[0046] 3. Under stirring (stirring speed is 100-500rpm), add about 100-200mL of the above-mentioned catalyst dilution to the first reactor, add raw materials ethylene and hydrogen to the reactor, adjust the amount of hydrogen added to control the molecular weight of polyethylene (the volume ratio of hydrogen to ethylene is 0.001-0.005:1), keep the pressure in the reactor at 0.2-0.8MPa after the addition of gaseous ethylene and hydrogen, control the temperature in the first reactor at 30-50°C, and control the reaction time at 0.1-1h;
[0047] 4. After the prepolymerization reaction, the reaction slurry discharged from the first reactor enters the second reactor, the temperature in the second reactor is controlled at 70-90° C., the pressure is controlled at 0.45-0.6 MPa (if necessary, raw materials ethylene and hydrogen can be added), and the second reactor is stirred (stirring speed is 100-500 rpm) for polymerization reaction for 2-8 hours, preferably 3-6 hours;
[0048] 5. After the polymerization is completed, the reaction slurry discharged from the second reactor is post-treated and the slurry is moved to a flash tank for product separation. The separated gas phase is sent to a recovery unit, and the separated solid polymer enters a degassing and drying unit, and the final product is obtained after drying.
[0049] The following is an explanation with reference to specific examples to prepare polyethylenes E1 to E5.
[0050] Example 1
[0051] Preparation of polyethylene E1: After nitrogen purging the reaction system, about 1L of hexane was added to the first reactor, and the temperature in the first reactor was maintained at about 35°C; in the catalyst preparation tank, the catalyst Y1 and the hexane were evenly mixed to make the concentration of TiCl4 0.1mmol / L to form a catalyst dilution; under stirring (stirring speed of 200rpm), about 180mL of the catalyst dilution was added to the first reactor, and the raw materials ethylene and hydrogen were added to the reactor (the volume ratio of hydrogen to ethylene was about 0.0035:1), and the pressure in the reactor was maintained at about 0.45MPa, and the pressure was controlled The temperature in the first reactor was 35°C, and the prepolymerization time was 25 min. After the prepolymerization, the reaction slurry discharged from the first reactor entered the second reactor, and the temperature in the second reactor was controlled at 75°C. The pressure in the reactor was controlled at 0.55 MPa by adding raw materials ethylene and hydrogen, and the polymerization reaction was carried out for 3 hours under stirring (stirring speed was 200 rpm). After the polymerization was completed, the reaction slurry discharged from the second reactor was transferred to a flash tank for product separation, and the separated gas phase was sent to a recovery unit, and the separated solid polymer entered a degassing and drying unit, and the final product polyethylene E1 was obtained after drying.
[0052] Example 2
[0053] Preparation of polyethylene E2: After nitrogen purging the reaction system, about 1L of hexane was added to the first reactor, and the temperature in the first reactor was maintained at about 40°C; in the catalyst preparation tank, the catalyst Y2 and the hexane were evenly mixed to make the concentration of TiCl4 0.22mmol / L to form a catalyst dilution; under stirring (stirring speed of 250rpm), about 150mL of the catalyst dilution was added to the first reactor, and the raw materials ethylene and hydrogen were added to the reactor (the volume ratio of hydrogen to ethylene was about 0.0035:1), and the pressure in the reactor was maintained at about 0.47MPa, and the pressure was controlled The temperature in the first reactor was 40°C, and the prepolymerization time was 35 minutes. After the prepolymerization, the reaction slurry discharged from the first reactor entered the second reactor, and the temperature in the second reactor was controlled at 78°C. The pressure in the reactor was controlled at 0.58MPa by adding raw materials ethylene and hydrogen, and the polymerization reaction was carried out for 3.5 hours under stirring (stirring speed was 250rpm). After the polymerization was completed, the reaction slurry discharged from the second reactor was transferred to a flash tank for product separation, and the separated gas phase was sent to a recovery unit, and the separated solid polymer entered a degassing and drying unit, and the final product polyethylene E2 was obtained after drying.
[0054] Example 3
[0055] Preparation of polyethylene E3: After nitrogen purging the reaction system, about 1L of hexane was added to the first reactor, and the temperature in the first reactor was maintained at about 45°C; in the catalyst preparation tank, the catalyst Y3 and the hexane were evenly mixed to make the concentration of TiCl4 0.36mmol / L to form a catalyst dilution; under stirring (stirring speed of 350rpm), about 165mL of the catalyst dilution was added to the first reactor, and the raw materials ethylene and hydrogen were added to the reactor (the volume ratio of hydrogen to ethylene was about 0.0035:1), and the pressure in the reactor was maintained at about 0.5MPa, and the first reactor was controlled. The temperature in the first reactor is 45°C, and the prepolymerization reaction time is 45 minutes; after the prepolymerization reaction, the reaction slurry discharged from the first reactor enters the second reactor, and the temperature in the second reactor is controlled at 80°C. The pressure in the reactor is controlled at 0.55MPa by adding raw materials ethylene and hydrogen, and the polymerization reaction is carried out for 4.5 hours under stirring (stirring speed is 350rpm); after the polymerization is completed, the reaction slurry discharged from the second reactor is transferred to a flash tank for product separation, and the separated gas phase is sent to a recovery unit, and the separated solid polymer enters a degassing and drying unit, and the final product polyethylene E3 is obtained after drying.
[0056] Example 4
[0057] Preparation of polyethylene E4: After nitrogen purging the reaction system, about 1L of hexane was added to the first reactor, and the temperature in the first reactor was maintained at about 50°C; in the catalyst preparation tank, the catalyst Y4 and the hexane were evenly mixed to make the concentration of TiCl4 0.4mmol / L to form a catalyst dilution; under stirring (stirring speed of 350rpm), about 125mL of the catalyst dilution was added to the first reactor, and the raw materials ethylene and hydrogen were added to the reactor (the volume ratio of hydrogen to ethylene was about 0.0035:1), and the pressure in the reactor was maintained at about 0.6MPa, and the pressure was controlled The temperature in the first reactor is 50°C, and the prepolymerization reaction time is 20 minutes. After the prepolymerization reaction, the reaction slurry discharged from the first reactor enters the second reactor, and the temperature in the second reactor is controlled at 85°C. The pressure in the reactor is controlled at 0.65MPa by adding raw materials ethylene and hydrogen, and the polymerization reaction is carried out for 5 hours under stirring (stirring speed is 350rpm). After the polymerization is completed, the reaction slurry discharged from the second reactor is transferred to a flash tank for product separation, and the separated gas phase is sent to a recovery unit, and the separated solid polymer enters a degassing and drying unit, and the final product polyethylene E4 is obtained after drying.
[0058] Example 5
[0059] Preparation of polyethylene E5: After nitrogen purging the reaction system, about 1L of hexane was added to the first reactor, and the temperature in the first reactor was maintained at about 30°C; in the catalyst preparation tank, the catalyst Y4 and the hexane were evenly mixed to make the concentration of TiCl4 0.5mmol / L to form a catalyst dilution; under stirring (stirring speed of 350rpm), about 105mL of the catalyst dilution was added to the first reactor, and the raw materials ethylene and hydrogen were added to the reactor (the volume ratio of hydrogen to ethylene was about 0.0035:1), and the pressure in the reactor was maintained at about 0.8MPa, and the pressure was controlled The temperature in the first reactor was 30°C, and the prepolymerization time was 30 minutes. After the prepolymerization, the reaction slurry discharged from the first reactor entered the second reactor, and the temperature in the second reactor was controlled at 75°C. The pressure in the reactor was controlled at 0.8MPa by adding raw materials ethylene and hydrogen, and the polymerization reaction was carried out for 6 hours under stirring (stirring speed was 350rpm). After the polymerization was completed, the reaction slurry discharged from the second reactor was transferred to a flash tank for product separation, and the separated gas phase was sent to a recovery unit, and the separated solid polymer entered a degassing and drying unit, and the final product polyethylene E5 was obtained after drying.
[0060] [Comparative Example]
[0061] Comparative Example 1
[0062] Taking Example 3 as a reference, catalyst Y3 was replaced with an equal amount of Ziegler-Natta catalyst (TiCl4 and triethylaluminum, Ti / Al molar ratio of 1:75), and the rest was the same as Example 3 to obtain polyethylene D1.
[0063] Comparative Example 2
[0064] Taking Example 3 as a reference, the catalyst Y3 was replaced by an equal amount of the catalyst Z1, and the rest was the same as Example 3, to obtain polyethylene D2.
[0065] Compared with catalyst Y3, catalyst Z1 does not add magnesium chloride to the main catalyst, but replaces it with an equal amount of titanium tetrachloride.
[0066] Comparative Example 3
[0067] Taking Example 3 as a reference, the catalyst Y3 was replaced by an equal amount of catalyst Z2, and the rest was the same as Example 3, to obtain polyethylene D3.
[0068] Compared with catalyst Y3, catalyst Z2 does not add diethylaluminum chloride as the co-catalyst, but uses an equal amount of triethylaluminum instead.
[0069] Comparative Example 4
[0070] Taking Example 3 as a reference, catalyst Y3 was replaced by an equal amount of catalyst Z3, and the rest was the same as Example 3, to obtain polyethylene D4.
[0071] Compared with catalyst Y3, the catalyst Z3 has a co-catalyst that is not supported by an alumina carrier, and triethylaluminum and diethylaluminum chloride are directly added.
[0072] Comparative Example 5
[0073] Taking Example 3 as a reference, the prepolymerization process step was omitted and a single reactor was used for preparation.
[0074] The specific steps are as follows: after nitrogen is purged into the reaction system, about 1L of hexane is added into the reactor, and the temperature in the reactor is maintained at about 80°C; in the catalyst preparation tank, the catalyst Y3 and the hexane are evenly mixed, and the concentration of TiCl4 is 0.36mmol / L to form a catalyst dilution liquid; under stirring (stirring speed is 350rpm), about 165mL of the catalyst dilution liquid is added into the reactor, and the raw materials ethylene and hydrogen are added into the reactor (the volume ratio of hydrogen to ethylene is about 0.0035:1), and the pressure in the reactor is maintained at about 0.55MPa, and the temperature in the reactor is controlled at 80°C, and the polymerization reaction time is 5h. After the polymerization is completed, the reaction slurry discharged from the reactor is moved to a flash tank for product separation, and the separated gas phase is sent to the recovery unit, and the separated solid phase polymer enters the degassing and drying unit, and the final product polyethylene D5 is obtained after drying.
[0075]
Product performance test
[0076] At least three representative samples were randomly selected from each experimental batch to ensure the reliability of the test results.
[0077] The viscosity average molecular weight is measured according to standard GB 1632.3-2010 (α=1.49).
[0078] The particle size is tested in accordance with ISO 13320:2020 using a Malvern particle size tester.
[0079] The specific test results are shown in Table 2.
[0080] Table 2 Polyethylene sample test results
[0081]
[0082]
[0083] As shown in Table 2, the viscosity-average molecular weight of the ultra-high molecular weight polyethylene obtained in the embodiment of the present invention is 1.45-1.55 million, the particle size is 60-90 μm, and the particle size distribution index (PDI) is 0.2-0.3, that is, it has a molecular weight of about 1.5 million, a particle size within 90 μm and a PDI less than 0.3, which is a high-quality ultra-high molecular weight polyethylene with fine particle size and consistent particle size distribution. In the comparative example, when the specific composition of the catalyst is changed (Comparative Example 1 to Comparative Example 4) or the prepolymerization process is not used (Comparative Example 5), although an ultra-high molecular weight polyethylene with a molecular weight of about 1.5 million can be obtained, the particle size of the polyethylene is relatively large, the particle size distribution index is greatly increased, and the particle size consistency of the polymer becomes poor.
[0084] The above are only preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be regarded as limiting the present invention, and the protection scope of the present invention should be based on the scope defined by the claims. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing ultra-high molecular weight polyethylene with uniform particle size distribution, characterized in that: The steps include: S1, adding hexane into the first reactor as a solvent, adding a catalyst, raw material ethylene and hydrogen into the first reactor to carry out a prepolymerization reaction; S2, after the prepolymerization reaction, the reaction slurry discharged from the first reactor enters the second reactor for polymerization reaction; S3, after the polymerization is completed, the reaction slurry discharged from the second reactor is post-treated to obtain a finished product; Wherein, the catalyst described in step S1 includes a main catalyst, a co-catalyst and an electron donor; The main catalyst is titanium tetrachloride doped with a magnesium compound; The co-catalyst is triethylaluminum and / or diethylaluminum chloride supported by alumina; The electron donor is a siloxane compound.
2. The method for preparing ultra-high molecular weight polyethylene with uniform particle size distribution according to claim 1, characterized in that: The molar ratio of the main catalyst, the co-catalyst and the electron donor is 1:50-100:1-10, preferably, the molar ratio of the main catalyst, the co-catalyst and the electron donor is 1:75-100:3-6; In the main catalyst, the molar ratio of the magnesium compound to titanium tetrachloride is 0.01-1:
1. Preferably, the molar ratio of the magnesium compound to titanium tetrachloride is 0.1-0.5:
1. The magnesium compound includes magnesium chloride, magnesium bromide, magnesium iodide, and diethoxymagnesium.
3. The method for preparing ultra-high molecular weight polyethylene with uniform particle size distribution according to claim 2, characterized in that: The co-catalyst is a mixture of triethylaluminum supported by alumina and diethylaluminum chloride supported by alumina, and the molar ratio of triethylaluminum to diethylaluminum chloride is 2:1-3.
4. The method for preparing ultra-high molecular weight polyethylene with uniform particle size distribution according to claim 3, characterized in that: The preparation method of alumina-loaded triethylaluminum and alumina-loaded diethylaluminum chloride is as follows: adding an alumina carrier to a solution containing triethylaluminum or diethylaluminum chloride, soaking for a certain period of time under stirring to allow triethylaluminum or diethylaluminum chloride to be uniformly adsorbed on the surface of the alumina, and drying and activating the loaded alumina carrier to obtain the product.
5. The method for preparing ultra-high molecular weight polyethylene with uniform particle size distribution according to claim 2, characterized in that: The electron donor is a siloxane compound, Selected from tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, methyltriethoxysilane, ethyltriethoxysilane, n-propyltriethoxysilane, monochlorotriethoxysilane, 3-chloropropyltriethoxysilane, methyltrimethoxysilane, ethyltrimethoxysilane, isobutyltrimethoxysilane, hexyltrimethoxysilane, dimethyldimethoxysilane, diisopropyldimethoxysilane, dicyclohexyldimethoxysilane, cyclohexylmethyldimethoxysilane, diphenyldimethoxysilane, phenylmethyldimethoxysilane.
6. The method for preparing ultra-high molecular weight polyethylene with uniform particle size distribution according to claim 1, characterized in that: In step S1, the catalyst is diluted with hexane to obtain a catalyst dilution solution, which is then added to the reactor, wherein the concentration of TiCl4 in the dilution solution is 0.1 to 10 mmol / L, preferably 0.1 to 1 mmol / L, and more preferably 0.1 to 0.5 mmol / L; And / or, the volume ratio of hydrogen to ethylene is 0.0001 to 0.01:1, preferably, the volume ratio of hydrogen to ethylene is 0.001 to 0.005:
1.
7. The method for preparing ultra-high molecular weight polyethylene with uniform particle size distribution according to claim 1, characterized in that: The reaction conditions for the prepolymerization reaction in the first reactor in step S1 are: the temperature in the reactor is controlled at 30-50° C., the pressure is controlled at 0.2-0.8 MPa, and the polymerization reaction time is controlled at 0.1-1 h. Preferably, the temperature in the reactor is controlled at 35-45° C., the pressure is controlled at 0.45-0.6 MPa, and the polymerization reaction time is controlled at 0.15-0.5 h.
8. The method for preparing ultra-high molecular weight polyethylene with uniform particle size distribution according to claim 1, characterized in that: The reaction conditions for the polymerization reaction in the second reactor in step S2 are: the temperature in the reactor is controlled at 70-90°C, the pressure is controlled at 0.2-0.8MPa, and the polymerization reaction time is controlled at 2-8h. Preferably, the temperature in the reactor is controlled at 75-85°C, the pressure is controlled at 0.45-0.6MPa, and the polymerization reaction time is controlled at 3-6h.
9. The method for preparing ultra-high molecular weight polyethylene with uniform particle size distribution according to claim 1, characterized in that: The post-treatment in step S3 is as follows: the slurry after the reaction is moved to a flash tank for product separation, the separated gas phase is sent to a recovery unit, and the separated solid phase polymer enters a degassing and drying unit, and the final product is obtained after drying.
10. An ultra-high molecular weight polyethylene obtained by the preparation method according to any one of claims 1 to 9, characterized in that: The viscosity average molecular weight of the ultra-high molecular weight polyethylene is between 1.45 million and 1.55 million, the particle size is between 60 and 90 μm, and the particle size distribution index is between 0.2 and 0.3.
Citation Information
Cited By
Production process of ultra-high molecular weight polyethylene
CN122127512A